[News Script: Allies meeting] - WBAP-TV (Television station : Fort Worth, Tex.) (1973)
Script from the WBAP-TV/NBC station in Fort Worth, Texas, relating a news story about secretary of state rogers who assured the North Atlantic allies at a meeting in Copenhagen that president Nixon will turn down any attempt by Russia's Leonid Brezhnev to settle major issues over their hands.